Mapping of areas degraded by oil wells through aero photometry producing region in Mossoró-RN - Jeronimo, Carlos Enrique de Medeiros; Oliveira, Alexsandro Albino Souza de (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2014)
Manage the mapping of the Municipality of Mossoró-RN, focusing on degraded by oil wells from the study by aerophotometry using Google Earth as a fundamental tool areas, creating a database to have an estimate of the degraded area, processing techniques digital images, besides allowing to analyze a scene in the various regions of study also enabled the integration of multiple data types, duly registered through that it was possible to create tables with static treatment for better understanding.